Evaluation of Efficiencies on the Gadoxetic Acid-enhanced MRI for Preoperative Assessment of Liver Metastases from Colorectal Carcinoma - Ogasawara, Katsuhiko; Iwata, Kunihiro; Nakagawa, Sadahiro; Moriya, Toshiharu (Japanese Journal of Radiological Technology, 2018)
The aims of our study were: 1) to evaluate efficiencies of gadoxetic acid-enhanced magnetic resonance imaging (Gd-EOB-MRI) for preoperative assessment of liver metastases from colorectal carcinoma, and 2) to compare them with other diagnostic imaging modalities. The subjects of the analysis were outpatients with advanced colorectal cancer who are at risk of developing liver metastases (initial setting: pre-test probability=20%). At initial setting, we performed a decision analysis to calculate numbers of true positive (TP), false negative (FN), false positive (FP) and true negative (TN) test results per 1000 patients of Gd-EOB-MRI and other imaging modalities (conventional contrast agent-enhanced MRI, contrast-enhanced CT and 18F-FDG PET/CT). From the result of decision analysis, we calculated the cost of detection per one patient with liver metastases (detection cost). Also, we calculated positive predictive value (PPV) and negative predictive value (NPV). Moreover, these values were defined as efficiencies in this study. In the initial setting, number of TP, FN, FP TN results and detection cost of Gd-EOB-MRI were 197, 3, 40, 760, and 224,032.8 Japanese Yen, respectively. Also, PPV and NPV were 83.1% and 99.7%, respectively. In comparison with other imaging modalities, efficiencies of Gd-EOB-MRI were superior to them, except detection cost. We consider that the efficiencies of Gd-EOB-MRI, which we had assessed are easy to understand and useful when they are used for explanation to patients.